Re-Legitimizing the Institution of Journalism: The Indian news media's response to the "Radia Tapes" scandal. (17th February 2016) - Chadha, Kalyani; Koliska, Michael
Abstract : In late 2010, a series of tapes containing damaging conversations between 30 Indian journalists and Niira Radia, leading lobbyist for major business interests, became public. The tapes revealed journalists across the entire Indian news industry violating fundamental professional norms and offering the lobbyist's clients scripted interviews, giving advice on how to place stories in media outlets, talking about writing columns relying on positions articulated by Radia, and even apparently conveying messages on behalf of political interests close to the lobbyist. This paper explores how Indian news media responded to these revelations that posed a threat to the institution of journalism due to the pervasiveness of normative breaches. We propose that the Indian news media's response can be understood as an attempt to repair the institutional myth of the profession broadly defined as the way in which the public views journalism and its norms, using strategies associated with image restoration.